2016
DOI: 10.1111/1365-2745.12587
|View full text |Cite
|
Sign up to set email alerts
|

Modification of plant‐induced responses by an insect ecosystem engineer influences the colonization behaviour of subsequent shelter‐users

Abstract: Summary 1.Herbivores that modify plant morphology, such as gall-forming insects, can disproportionately impact arthropod community on their host plants by providing novel habitats and shelters from biotic and abiotic stresses. These ecosystem engineers could also modify plant chemical properties, but how such changes in plant quality affect the behaviour of subsequent colonizers has rarely been investigated. 2. We explored how an initial infestation of the tall goldenrod (Solidago altissima) by an ecosystem en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…), and have been shown to occur in both herbaceous and woody species (Gonzalez‐Megias and Gomez , Ohgushi , Uesugi et al. ). The indirect plant‐mediated interactions can have unexpected consequences for plant fitness, if they result in increased or decreased resistance toward more harmful herbivores (Kessler and Baldwin , McArt et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and have been shown to occur in both herbaceous and woody species (Gonzalez‐Megias and Gomez , Ohgushi , Uesugi et al. ). The indirect plant‐mediated interactions can have unexpected consequences for plant fitness, if they result in increased or decreased resistance toward more harmful herbivores (Kessler and Baldwin , McArt et al.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in plant physiology caused by one herbivore species can influence the quality and quantity of the plant as a food source for other species. Such plantmediated indirect interactions can occur between herbivore species that are temporally separated (Van Zandt and Agrawal 2004, Poelman et al 2008, Hernandez-Cumplido et al 2016, or attack different parts of the same host plant (McArt et al 2013, Arce et al 2017, and have been shown to occur in both herbaceous and woody species (Gonzalez-Megias and Gomez 2003, Ohgushi 2005, Uesugi et al 2016. The indirect plantmediated interactions can have unexpected consequences for plant fitness, if they result in increased or decreased resistance toward more harmful herbivores (Kessler and Baldwin 2004, McArt et al 2013, Machado et al 2018, or disruption of important mutualistic interactions (Kessler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Mirroring research on externally feeding herbivores, where HIPVs have been investigated from the egg-laying stage ( Hilker and Fatouros, 2015 ), comparable information is needed in galler–plant–parasitoid/inquiline interactions including stages such as tissue damage by ovipositor probing, egg laying, damage by larval mandibles, and finally gall induction. (3) Metabolic plasticity can occur in host-plant–galler interactions vis-a-vis different gallers and plant genotypes ( Uesugi et al, 2013 , 2016 ), resulting in varied responses that must, therefore, be interpreted within the context of the specific interactants. (4) We need to understand correlation networks of VOCs produced by plants under a variety of circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In S. altissima attacked by the rosette gall-midge Rhopalomyia solidaginis , emissions of terpenes such as copaene and β-pinene increased post-galling ( Uesugi et al, 2016 ); these attracted herbivorous beetles whose presence facilitated galler performance, suggesting that VOC emission patterns must be viewed in an integrated manner.…”
Section: Impact Of Gall Makers On Plant Volatilesmentioning
confidence: 99%
“…A consequence of directed behavior is that individual insects can actively choose not only particular plant genotypes, but also plants experiencing a particular physiological circumstance, age or habitat (Janz et al, 2005;Knolhoff & Heckel, 2014). For example, individuals of various insect species specifically search for individuals within the host species range that are under drought stress or are well hydrated (Carr et al, 1998;Kolb et al, 2016), are previously damaged by abiotic or biotic agents, or, conversely, host individuals that are undamaged (Roininen et al, 1997;Powell et al, 2012;Uesugi et al, 2016), or are of a particular age category (Kearsley & Whitham, 1989). Furthermore, insects may prefer plants that, by chance, are located on a site that provides higher nutritional quality or, conversely, may avoid plants that harbor predators (Stamp & Bowers, 2000) or are near other plant species that emit volatile repellents (Barbosa et al, 2009).…”
Section: Forummentioning
confidence: 99%